Perceptions of tourism impacts and community resilience to natural disasters. Issue 2 (14th March 2016) - Tsai, Chung-Hung; Wu, Tsung-chiung (emily); Wall, Geoffrey; Linliu, Shu-Chuan
ABSTRACT: Evidence since at least the 1990s suggests that global climate patterns have undergone dramatic changes, often resulting in weather-induced natural disasters that have caused widespread environmental damage. Such conditions raise serious threats to communities that are dependent on natural resources and ecosystem services for tourism development. Communities located in high-risk disaster regions face greater challenges in developing a tourism economy that is both resilient and sustainable. Residents in these communities live with a constant awareness of external threats and try to build a degree of resilience that includes traditional disaster prevention measures and a long history of post-disaster reconstruction. It is necessary to understanding the relationships between tourism and community resilience to address planning and development goals in an era of increasing climate uncertainty. Three communities are examined that are regularly exposed to the threats of typhoons and flooding and are located within National Scenic Areas in Taiwan. In-depth interviews with community leaders and surveys of residents were undertaken. Residents with high potential to experience natural disasters generally have high degrees of awareness of various forms of tourism impacts. Their perceptions of tourism impacts are positively correlated with community resilience. The strongest relationships are between a perception of the positive economic impacts from tourism and the local capacity for undertaking adaptive responses; and between an awareness of the environmental impacts of tourism and the perceived fragility of their environment. Empowering community resilience usually requires long-term capacity building and is correlated with all three types of perceived tourism impacts. Deconstruction of the special experiences of disaster-prone tourism destinations provides a more nuanced insight into the relationships between community knowledge and awareness of resilience needs and the role and impacts of tourism. This, in turn, facilitates understanding of community tourism development in the face of contemporary changes in weather and climate.